Space vector pulse-width modulation theory and solution for Z-source inverters with maximum constant boost control - Cai, Xu (2013)
The theory of space vector pulse-width modulation (SVPWM) technique for the three-phase Z-source inverter has been introduced in detail, and a novel implementation scheme based on the maximum constant boost control method is presented in this paper. Like the traditional carrier-based maximum constant boost control strategy, the proposed control method is able to achieve the maximum voltage boost ability while always keeping the shoot-through duty ratio constant. Besides, it inherits the advantages from the SVPWM technique. Compared with carrier-based strategies, it has wider linear operation range and is easier for digital implementation. The number of switching transition in each switching cycle is reduced, which significantly decreases switching losses. To investigate the advantages of lessening switching losses, three optimal switching patterns are proposed and compared with the carrier-based strategy. It is demonstrated that the number of switching transition can be reduced by 60% at most by the proposed SVPWM-based control method. All the theoretical analysis has been validated by the simulation results in MATLAB/Simulink at last.